Studi Faktor Determinan Keputusan Investasi Generasi Milenial Pada Aset Kripto - Khaerunnisa Nur Fatimah Syahnur; Syarief Dienan Yahya (AkMen JURNAL ILMIAH, 2022)
The growth trend of investing in crypto assets dominated by the millennial generation is increasing every year, making research that analyzes the determinants of this phenomenon is increasingly interesting to study. This study aims to try to analyze the factors that influence the millennial generation's investment decisions in crypto assets through gender, age group, and financial knowledge as independent variables. This study involved 252 millennial respondents who had read, researched, or understood about crypto assets. The research data was processed using a binary logistic regression model using statistical analysis software SPSS (Statistical Package for the Social Sciences). The results show that partially gender and age group variables have no effect on millennial generation's investment decisions in crypto assets. On the other hand, the financial knowledge variable has a significant influence on the millennial generation's investment decisions on crypto assets